Successful Percutaneous Intervention of the Left Main and Right Coronary Arteries in the Same Session - Abdullah Nabi Aslan; Serdal Baştuğ; Serkan Sivri; Cenk Sarı (Sakarya Tıp Dergisi, 2017)
Left main coronary artery (LMCA) stenosis is a relatively infrequent but important cause of symptomatic coronary artery disease. Patients who have LMCA stenosis experience a high rate of complications during or shortly after catheterization. In this case, we present a 84 years old woman with subacute inferior myocardial infarction and confirmed diagnosis of both LMCA and right coronary ostial severe stenosis who was successfully managed with percutaneous coronary intervention in the same session due to the sudden development of cardiogenic shock.ÖZETSol ana koroner arter (SAKA) darlığı semptomatik koroner arter hastalığının önemli fakat nispeten nadir bir sebebidir. SAKA darlığı olan hastalar kateterizasyon esnasında veya hemen sonrasında ortaya çıkabilecek yüksek komplikasyon riski altındadır. Bu vakada subakut inferior miyokard enfarktüsü ile prezente olan, koroner anjiyografi sonucu SAKA ve sağ koroner arterde ciddi osteal lezyon saptanan ve ani kardiyojenik şok geliştiği için aynı seansta hem SAKA hem de sağ koroner artere stent takılan 84 yaşında bir erkek hasta sunulmaktadır.